Knowledge, attitude and practices regarding HPV vaccination among medical and paramedical students in North India - Gupta, Himanshi; Sharma, Priya; Dubey, Swati; Gupta, Uma; Vikram, Aditya (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To assess the knowledge, attitude and practices regarding HPV vaccination among medical and para medical students in North India. Results: A total of 391 respondents were enrolled in the study with mean age of 24.39±4.27 years. The overall knowledge level of respondents in the study was satisfactory around 69%. Majority of respondents favours need for more awareness programmes regarding HPV vaccination, implementation of education on HPV infection at schools and colleges, inclusion of HPV vaccination in National Immunisation Schedule and provision to provide vaccination at schools and colleges. In regard to practice, 78.5% respondents either underwent or were willing to undergo vaccination. Reason for non-vaccination were mainly fear of side effect (23.2%), cost (18.8%), doubts about efficacy (10.4%) and others. Methods: This study is Cross sectional study conducted among 391 medical and nursing students after obtaining ethical approval from the Institute’s Ethics committee. Data was analyzed using Statistical Package for Social Sciences 21.0. Independent samples t-test and ANOVA were used to compare the data. Correlation between knowledge, attitude and practice scores was assessed using Pearson correlation coefficient. Conclusions: The study concludes, not only the students but a health care professional lacks appropriate knowledge regarding HPV and cervical cancer.